Effect of Salt and Nutrient Medium on Phosphorus Solubilization Potential of Fungi Isolated from Salt-affected Soils - Chandra, Priyanka; Rai, Arvind Kumar; Basak, Nirmalendu; Sundha, Parul; Singh, Awtar; Prajapat, Kailash; Dhuli , Pooja; Yadav, Rajender Kumar (Journal of Soil Salinity and Water Quality, 2025)
Salinity is one of the most severe environmental constraints that limit agricultural productivity. Exploiting microorganisms with nutrient solubilizing and plant growth−promoting potential is an affordable natural approach to salinity alleviation. The current study was designed to isolate and screen salt−tolerant P−solubilizing fungi from salt−affected soils and optimize their growth parameters for future development as bioinoculants. Fifteen salt−tolerant P−solubilizing fungal isolates were evaluated. Fungi grown in potato dextrose medium (PDM) produced more biomass than those grown in Pikovskaya’s medium, but the results varied depending on the type of fungi. The biomass of the isolates decreased as the NaCl concentration increased. The results show a wide range of significant variations in the P−solubilization efficiency of salt−tolerant fungi. Quantitative estimation of P−solubilization significantly affected the interaction between fungal isolates × medium, while all the isolates demonstrated high P−solubilization potential (p ≤ .05). Fungal isolates also reduced the pH because of high organic acid production. The quantitative assay revealed the presence of intra/extracellular acid and alkaline phosphatase activity at variable titre. The study revealed the presence of salt−tolerant P−solubilizing fungi in the rhizosphere of crops growing in saline areas. Therefore, PDB is a better medium for bulk production of fungi for developing bio−inoculants.